(untitled) (Journal of Informatics Education and Research, 2025)
This study examines the effects of dynamic pricing methods on consumer loyalty within the e-commerce industry. As price changes become prevalent, firms utilize algorithmic pricing models to enhance revenue and market competitiveness. The effects of these techniques on consumer trust, retention, and happiness continue to be a topic of discussion. This study utilizes empirical analysis to evaluate consumer reactions to dynamic pricing methods, focusing on characteristics such as perceived fairness, transparency, and purchasing behavior. The study examines real-world data and consumer emotion to see if dynamic pricing promotes loyalty or results in customer attrition. The results offer significant insights for e-commerce platforms to reconcile profitability with sustained client engagement. The research underscores potential problems and ethical implications associated with the use of dynamic pricing structures. The study finishes with recommendations for firms on implementing these techniques while maintaining consumer trust and pleasure.